Pengaruh asupan Fe, vitamin A, vitamin B12, dan vitamin C terhadap kadar hemoglobin pada remaja vegan - Damayanti Siallagan; Prita Dhyani Swamilaksita; Dudung Angkasa (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2016)
Background: Vegan has become a diet that started to be many people's choice. Low intake of iron and vitamin B12 is factors that can cause anemia in vegan. On the other side vegans often consume vegetables and fruits that contained high of vitamin A and vitamin C which helps the absorption of iron, that can help prevent anemia.Objective: The purpose of the research know the effect of the intake of iron, vitamin A, vitamin B12, vitamin C on hemoglobin (Hb)levels in young Buddhist vegan Pusdiklat Maitreyawira.Method: This research uses cross-sectional design. The population in this study are all adolescent vegan in the Buddhist Pusdiklat Maitreyawira. Samples in this study were 31 peoples. Independent variable is an intake of iron, vitamin A, vitamin B12, and vitamin C was obtained by SQ-FFQ, while the dependent variable was Hb with hemoglobin testing system quick-check set. Analysis of the data in this study using Pearson correlation and multiple linear regression.Results: There is a relationship intake of iron (p=0,000), vitamin B12 (p=0,037), and vitamin C (p=0,000) to Hb level of adolescent vegan in Buddhist Pusdiklat Maitreyawira, there is no relationship intake of vitamin A with a Hb level of adolescent vegan (p=0,220). The result of multivariate analysis using multiple regression analysis of the variables that most influence haemoglobin levels of adolescent vegan are the intake of iron and vitamin C. Each increase of 1 mg Fe intake will increase the Hb concentration as much as 0.013 g/dl and increase of 1 mg of vitamin C intake will increase Hb levels as much as 0.002 g/dl.Conclusion: Iron and vitamin C intake is the most influence factors to hemoglobin levels of adolescent vegan in Buddhist Pusdiklat Maitreyawira.